1981
DOI: 10.1007/bf00278713
|View full text |Cite
|
Sign up to set email alerts
|

Properdin factor B polymorphism in continental Italy and Sardinia

Abstract: A sample of healthy unrelated individuals (882 from Continental Italy and Sicily, and 139 from Sardinia) were typed for HLA and Bf polymorphisms. Bf gene frequencies in Continental Italy and Sicily show an intermediate position among European populations, with Lapps on one side and Basques on the other side; while a very peculiar pattern is observed among Sardinians, with an impressive similarity with French Basques and with the highest F1 gene frequency so far observed. The HLA:Bf gametic associations in Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…[1982] the C3 system (table III). However, there was a highly significant difference in the Bf system between continental Italy (in cluding Tuscany) and Sardinia (table IV), as previously reported by Malavasi et al [1981] and Davrincheet al [1984],…”
Section: Resultssupporting
confidence: 65%
“…[1982] the C3 system (table III). However, there was a highly significant difference in the Bf system between continental Italy (in cluding Tuscany) and Sardinia (table IV), as previously reported by Malavasi et al [1981] and Davrincheet al [1984],…”
Section: Resultssupporting
confidence: 65%
“…Except for Norwegian Lapps where it is missing, the BF*S07 allele frequency is the lowest ever reported in Europe. A recent study of BF polymorphism in Sardinia [Malavasi et al, 1981] reported slightly different val ues according to BF*S, *F, and *S07 fre quencies (table II). A surprisingly higher frequency was reported for the *S07 allele (BF*S07 = 0.043).…”
Section: Bf Polymorphismmentioning
confidence: 99%
“…Nonetheless, we have also seen how the mouse system benefited from the existence of a CD38 KO model, enabling an accurate and causative comparison with the normal counterpart. The search for naturally occurring CD38-individuals was attempted in humans by analyzing more than 5,000 blood samples from newborns, reproducing the experience gathered with individuals lacking complement C2 and C4 [100]. In the Italian sample analyzed, none of the newborns was CD38j, suggesting that the absence of CD38 is incompatible with life (F. Malavasi, unpublished results).…”
Section: Discussionmentioning
confidence: 99%